(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The objective of the research is to prove that the work and creations of Jubran form a special literary imprint on the level of the included form of the verified artistic performance , through the correlation between form and content. He added a creativity and a poetic splash that harmonized with the rest of the components to form a poetic painting with a special rhythm , and to reveal the positive and negative aspects of jubran’s poetic experience, the research adopted descriptive analytical method through the technical analysis of the poem "the processions", Speaking of the structure of the poetic text intertwined between three movements that each one of them has a distinct structure at the level of the jubranic form and content, And semantic relations, And the various methods in it (Direct preaching method and mental guidance, and the creative method), And its philosophical content, And the language of Gibran in this poem, and the different indications of each of its symbols, And about the rhythm and poetic image with its components, The most notable results were : That Gibran is the first poet of modernity, and he is the first to rebel against the monotonous music of sound and rhyme music to the variety of metrics in the poetic verse, and If this indicates anything , it indicates the spontaneity of the poetic splash that does not need to be sculpted or strictly made, He is aware of poetry historical extension, , he does not abolish the old for being an old, But because life imposes such change and novelty ,he is building up an effective person, , In a manner that we may call challenging ease, For the ease of his words , and the ability to read out various semantics of it. His phraseology is dominated by the rural style , jubran is born out of all sides lived life, It was his emigration that drove him to work, Balanced work that creates a beautiful person whose dignity is attained in the light of these perceptions, To paint the shades of this painting was the harmony between words and music that reflected the inner rhythm of jubran , and if knowledge was a lock ,asking is the key to it , so who is jubran?, is he the GODO of hope, Or is he an equivalent to Christ, peace be upon him , sent to save humanity !!